Winning in asia : strategies for competing in the new millennium - Williamson, Peter J. ([S.l.] : Harvard Business Review Press, 2004)
This is the first book to spell out exactly what multinational and local Asian firms must do to compete successfully in post-crisis Asia. While the Asian economy used to depend primarily on exports, today the local Asian market is demanding and consuming more goods. The make-up of competition locally is shifting from national fiefdoms to cross-border competition. And China's rapid development is changing how competition is played altogether. "Winning in Asia" explores these new business realities in Asia, and explains why there will be no going back to the "Asian norm" of the 80s and 90s. Most importantly, it tackles head-on the critical issue of what companies - both local Asian businesses and multinational corporations operating in Asia - must do and how they must change in order to compete successfully in the next round of Asian competition.
Keywords: Business enterprises; Competition, International; East Asia; Industrial management; International business enterprises; Southeast Asia